Interpretation of Paleo-Channel Based on Shallow Seismic Reflection Record in Banten Bay, Banten Province - Yogi Noviadi (BULLETIN OF THE MARINE GEOLOGY, 2016)
The objective of this study is to find out the pattern of paleo channel which was formed in Banten Bay and its surrounding.  The aims are to find out the paleo-channel pattern at study area. The study methods are including vessel positioning, and shallow seismic reflection work. Vessel positioning method is to locate the exact position of seismic work     when recording the data from single channel of shallow seismic reflection. Seismic line orientations are determined by regional geological setting of the area. Trend of seismic lines are dominantly north – south. In order to get the seismic data which could give geological setting configuration, seismic lines should be perpendicular to the strikes of the sediments.Based on the calculation of velocity of seismic refraction in sea water 1,500 meters/second, while within sediment 1,600 meters/second, it could be concluded that the paleo chanels were more or less in 32 meters below sea floor depth.This layer was the system that occur during the process of an interglacial on the Sunda Shelf when it was still a part of land that connects the Java, Sumatra and Kalimantan Islands. Paleo-channel deposits are characterized by subparalel - chaotic reflection character with a thickness between 5-35 meters.Keywords: Paleo-channels, seismic records and Banten BayMaksud dari penelitian ini adalah untuk mengetahui pola sungai purba yang terdapat di Teluk Banten dan sekitarnya, yang tujuannya adalah untuk mengetahui pola penyebaran alur sungai purba di daerah penelitian. Metode penelitian terdiri dari penentuan posisi kapal dan penelitian  seismik pantul dangkal. Penentuan posisi kapal berguna untuk menemukan posisi yang tepat saat merekam data oleh perlatan seismik saluran tunggal dangkal. Lokasi lintasan seismik disesuaikan dengan kondisi geologi daerah penelitian. Arah lintasan seismik pada umumnya berarah utara – selatan. Untuk mendapatkan data seismik yang bisa memberikan konfigurasi kondisi geologi, lintasan seismik harus tegak lurus terhadap kedudukan lapisan batuan.Berdasarkan cepat rambat gelombang seismik di air laut 1.500 meter/detik, dan sedimen 1.600 meter/ detik, dapat disimpulkan bahwa alur purba kurang lebih berada pada kedalaman  32 meter di bawah dasar laut.Lapisan ini merupakan sistem pengendapan yang terjadi selama proses interglasial di Paparan Sunda yang pada saat itu masih  merupakan bagian dari daratan yang menghubungkan P. Jawa, Sumatera dan P. Kalimantan. Endapan alur purba  dicirikan dengan pola refleksi subparalel sampai tidak beraturan dengan ketebalan antara 5-35 meter.Kata kunci: Alur purba, rekaman seismik dan teluk Banten